Cultural dialogue and its premises in colonial Peru: the case of worshipping sacred objects - Brosseder, Claudia (Journal of the economic and social history of the Orient, 2012)
Abstract This article examines, from both an indigenous and a Spanish perspective, one of the central aspects of the history of evangelization in the colonial Andes: the discourse about “representation” and “embodiment.” By centering on this discourse and by distilling Incan, pre-colonial Andean, and colonial Andean notions from colonial texts, the article contributes to our understanding of the differences between Spanish and Andean concepts of religion and shows how mutual assimilation shaped the evolution of a colonial Andean religion.